An assessment of electrofishing effects on Capoeta capoeta in a controlled environment (salinity and temperature) - Parisa Maleki; Rahman Patimar; Hojatallah Jafariyan; Rassul Ghorbani (بوم‌شناسی آبزیان, 2015)
The purpose of this study was to investigate the effect of voltage, salinity and temperature on the performance of electrofishing. Number 850 pcs Capoeta capoeta of Chehel Chay river of Golestan province fishing and transported to the laboratory. Distance from the anode, cathode and anode distance during testing, respectively, 10 cm and the 120 cm. Range of length and weight of the fish test species in order Capoeta capoeta 11.53± 0.61cm and 13.701± 5.303 gr. Electric shocks were applied to the individual fish on the three voltages of 15, 45 and 135 volts and three temperatures of 10° c, 20° c and 30° c and three salinities of 0.5, 2 and 4 gr/liter. Time to anesthesia and recovery were recorded for each fish. Statistical analysis using One-way Anova, Duncan and LSD test. Comparison showed that the average duration of anesthesia voltages and temperatures and the salinities are significantly different. Maximum anesthesia time for Capoeta capoeta abtain from the salinity 2 gr/liter, temperature 10° c, Voltage 15 volt with a mean (7.81±0.88 s) and minimum abtain from salinity4 gr/liter, temperature 20° c, voltage 135 volt, with mean (1.18± 0.09 s). Maximum of the recovery time to Capoeta capoeta abtain from Salinity 0.5 gr/liter, temperature 30° c, Voltage 135 volt with a mean (159.46± 16.17 s) show and minimum abtain from salinity 0.5 gr/liter, temperature 20° c, voltage 15 volt with a mean (44.29±9.11 s).